Electrochemical Determination of Se(Iv) in Food and Water Samples Using Reduced Graphene Oxide and Gold Nanoparticle-Modified Glassy Carbon Electrodes - Pizarro-Konczak, J; Segura-Segura, R; Segura-Segura, R; Godoy-Gonzalez, F; Godoy-Gonzalez, F; Paz de la Vega-Quiroz, A; Paz de la Vega-Quiroz, A; Liendo-Ibarra, F; Liendo-Ibarra, F; Penagos-Llanos, J; Penagos-Llanos, J (Elsevier Ltd, 2025)
A novel electrochemical sensor for Se(IV) determination is proposed using a glassy carbon electrode (GC) modified with electrochemically reduced graphene oxide (rGO) and electrochemically generated gold nanoparticles (AuNPs). The GC/rGO/AuNPs electrode was characterized by cyclic voltammetry (CV) and scanning electron microscopy (SEM). The results showed a homogeneous distribution of gold nanoparticles with sizes ranging from 32.48 to 73.49 nm. Chemical and electrochemical parameters were optimized as follows: accumulation potential (Eacc) of -0.80 V (vs Ag/AgCl), accumulation time (tacc) of 120 s, frequency of 15 Hz, and 15 reduction cycles for rGO deposition. Using square wave anodic stripping voltammetry (SWASV), a limit of detection (LOD) of 0.63 μg l-1 and a limit of quantification (LOQ) of 2.11 μg l-1 were obtained. The method showed good reproducibility, repeatability, and accuracy. Finally, the proposed method was successfully applied to legume (Phaseolus vulgaris and Lens culinaris) and water samples, with results statistically comparable to electrothermal atomic absorption (ET-AAS). © 2025